Upaya Peningkatan Profitabilitas Dalam Pengelolaan Kredit Di Masa Pandemi Covid-19 Pada BPR - Fermina Julian Ade Purwanto; Endang Kartini Panggiarti; Agustina Prativi Nugraheni (Akuntansi dan Manajemen, 2022)
The purpose of this study is to find out the bad credit management implemented by PT. BPR BKK Muntilan (Perseroda), to find out the credit management mechanism of PT. BPR BKK Muntilan (Perseroda), to find out the profits obtained and efforts to increase profitability. Collection techniques by means of observation in the field of credit and the field of funds, interviews conducted by 2 speakers in the field of credit and the field of funds and 1 resource person in the field of marketing, documentation with several employees related to profitability in credit management and literature studies. This type of case study research approach with qualitative descriptive analysis that explains and describes actual events without being engineered in narrative form. The results showed that the management of bad loans implemented by PT BPR BKK Muntilan (Perseroda) in accordance with the applicable provisions and its application was good, but there were obstacles in the management of bad loans so that it carried out several elements of internal control, credit management mechanisms implemented and profits obtained based on profitability ratios and efforts made to increase profitability during the Covid-19 pandemic.